Status of soluble vascular cell adhesion molecule-1 in knee osteoarthritis among type 2-diabetic postmenopausal women - Shrivastava, Reetika; Singh, Neelima; Chandel, Y. S.; Dhakad, R. K. S.; Rathore, Vedika; Shrivastava, Swati (International Journal of Research in Medical Sciences, 2017)
Background: Knee osteoarthritis is the most common form of joint disorder and a leading cause of pain and functional disability among elderly female population. Type 2-diabetes is frequently reported comorbidity in elderly female patients with knee osteoarthritis. VCAM-1 is emerging as a strong and independent predictor for severe osteoarthritis. VCAM-1 is an inducible cell surface sialo glycoprotein and mediates heterotypic cellular aggregation. Therefore, the aim of this study is to assess the role of soluble vascular cell adhesion molecule-1 at the onset of knee osteoarthritis among type 2 diabetic postmenopausal women. Methods: The present study includes 100 type 2-diabetic female subjects of age above 50 years as cases and 100 normal healthy female age matched individuals as controls. Osteoarthritis of knee was ascertained using the American college of rheumatology classification criteria. Serum soluble VCAM-1 concentration was measured by ELISA method in all 200 subjects. Biochemical parameters-Fasting blood sugar and lipid profile were measured using Mind ray BS-400 and HbA1c was measured by turbidimetric immunoassay method. Statistical analysis was made by student independent sample t-test. Correlation was determined by using spearman’s rank correlation coefficient. Results: Serum level of soluble VCAM-1 was found statistically highly significant (p<0.001) in type 2 diabetic postmenopausal women having early stage of knee osteoarthritis as compared to control healthy subjects. The mean levels of fasting blood sugar, HbA1c, total cholesterol, TG, LDL-C and VLDL-C were also found significantly increased while HDL-C was found significantly decreased in cases as compared to controls. Conclusions: The increased level of soluble VCAM-1 in type 2 diabetic subjects shows active inflammation or cartilage damage. Therefore, it can be used as an early biomarker for osteoarthritis among type 2 diabetic postmenopausal women.